2010
DOI: 10.1016/j.gca.2010.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Relative chronology of crust formation on asteroid Vesta: Insights from the geochemistry of diogenites

Abstract: International audienceThe eucrites and diogenites are meteorites that probably originate from asteroid 4-Vesta. The upper part of the crust of this body is certainly composed of eucrites which are basaltic or gabbroic rocks. Diogenites are ultramafic cumulates whose relationships with eucritic lithologies are unknown. Here, we show that the orthopyroxenes of some diogenites display very deep negative Eu anomalies (Eu/Eu* close to 0.1 or lower). The contamination of the parental magmas of diogenites by melts de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
156
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(163 citation statements)
references
References 49 publications
5
156
1
1
Order By: Relevance
“…Ba and Sr abundances and sometimes anomalous REE distributions (e.g., Barrat et al, 2010). Therefore, 210 only two mildly weathered Saharan ureilites were selected for this study.…”
Section: Explanation 181mentioning
confidence: 99%
See 1 more Smart Citation
“…Ba and Sr abundances and sometimes anomalous REE distributions (e.g., Barrat et al, 2010). Therefore, 210 only two mildly weathered Saharan ureilites were selected for this study.…”
Section: Explanation 181mentioning
confidence: 99%
“…Only these data and the P abundances of the unleached fractions will be 207 used in the following sections and drawn in the various figures. In contrast with Antarctic samples, the hot 208 desert finds contained secondary phases such as barite, which are not easily leachable and account for high 209Ba and Sr abundances and sometimes anomalous REE distributions (e.g., Barrat et al, 2010). Therefore, 210 only two mildly weathered Saharan ureilites were selected for this study.…”
mentioning
confidence: 99%
“…Specifically, they predicted shallow dikes with widths of $1 m and vertical extents of <10 km and/or deep dikes with thicknesses 3 m and lateral extents 30 km. In addition, Barrat et al (2010), who performed a detailed study of the trace-element chemistry of diogenites which suggests that their petrogenesis is more complex than that of simple early crystallization products, proposed that Vesta's diogenites possibly formed as later-stage plutons injected into a eucrite crust. More recently, Keil and Wilson (2012) suggested that there may be many sill-like intrusions at the base of Vesta's lithosphere.…”
Section: Formation Of Brumalia Tholusmentioning
confidence: 99%
“…However, it is possible that the Albalonga fault pre-dates the end of Vesta volcanism, and thus that the material that injected the fault could have been sourced by either the magma plume theorized by Raymond et al (2013) to have formed the Vestalia Terra plateau, from the sill-like intrusions Keil and Wilson (2012) projected to be at the base of the vestan lithosphere or from one of the diogenitic intrusions into eucritic crust predicted by Barrat et al (2010). While the orientation of Albalonga Catena and the other two Vestalia Terra pit crater chains is roughly consistent with that of the equatorial troughs, it is possible that their underlying faults pre-date the Rheasilvia impact.…”
Section: Formation Of Brumalia Tholusmentioning
confidence: 99%
See 1 more Smart Citation